The avenues of my city: observations on the nomenclatures (Research, Society and Development, 2019)
The spaces designed and built by the people have lives and tell stories. The environment inhabited by people is a representation of their identity and culture represented aesthetically. Names of sites may be associated with diversities of taxonomic classification. Therefore, the article aims to point out some historical, empirical and linguistic elements of the microtoponymy of the city of Anápolis (GO), through the official names of the main avenues of the city. For this, a bibliographical research was carried out on toponymic theories, on the historical view of the city. As a result, it was noticed that, in the selected sample, the studied avenues have two taxonomic categories that are: Corotoponimos and Antropotonimos. Both categories were discussed in light of the recorded history of Anápolis and also with perceived empirical elements on nomenclatures.